2022
DOI: 10.1080/10717544.2022.2115165
|View full text |Cite
|
Sign up to set email alerts
|

Rapid oral transmucosal delivery of zaleplon–lavender oil utilizing self-nanoemulsifying lyophilized tablets technology: development, optimization and pharmacokinetic evaluation

Abstract: Based on the administration convenience, transmucosal buccal drug delivery allows special strength points over peroral routes for systemic delivery. It could achieve local or systemic effect and boost drugs’ bioavailability for agents with first pass metabolism. The current study aimed to manufacture and optimize a lavender oil–based nanoemulsion loaded with zaleplon and incorporate it into fast-disintegrating tablets to promote its dissolution and oral bioavailability via oral mucosa. Zaleplon-loaded nanoemul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…(Because the strength was recalibrated). 18 Mucoadhesive Force (N) = mucoadhesive strength ( gm ) × 0.0098…”
Section: Mucoadhesive Strength Studymentioning
confidence: 99%
“…(Because the strength was recalibrated). 18 Mucoadhesive Force (N) = mucoadhesive strength ( gm ) × 0.0098…”
Section: Mucoadhesive Strength Studymentioning
confidence: 99%
“…Furthermore, previous studies have found that local drug delivery can alleviate several problems, such as first-pass metabolism and gastrointestinal degradation. 26,27 However, subcutaneous implantation of longacting systems must be determined whether it can provide sustained drug delivery to treat acute cardiac allograft rejection.…”
Section: Introductionmentioning
confidence: 99%